(untitled) (Nepal Medical College Journal, 2022)
Stunting or poor linear growth affects about 25% of children under five globally. Poor linear growth may occur due to lack of nutrients or due to hormonal influences. This study has investigated the relationship between maternal stature, household socio-economic status and linear growth among children below two years of age visiting the immunization clinic at an urban tertiary hospital in Kathmandu, Nepal. An observational cross-sectional analytical study was carried out through a face-to-face interview of mothers with a pretested standardized proforma. Anthropometric measurement of mother and child dyads was carried out to assess the nutritional status. Nutritional anthropometry tool in Epi-Info version 7.2.0.2 was used to calculate height-for-age z-scores (HAZ) based on the WHO 2007 reference data. A cut-off of –2 z-scores was used to define stunting (<-2HAZ). Linear regression was used to study the correlation between maternal anthropometric indices and HAZ scores. Univariate logistic regression was used to assess potential predictors. Among 396 mother-child dyads, with 186 female children, the prevalence of low birth weight was 7% (95% CL: 5.1% to 10.3%) and stunting was 4.5% (95% CL: 2.9 to 7.0). Proportion of mothers with short stature (<145 cm) was 7.5% (95% CL: 5.3% to 10.5%). Maternal height had a higher correlation with HAZ in comparison to weight (r 0.24, P<0.0001 vs 0.09, P=0.04). The mean HAZ score among infants (<6 months) was 1.25, 0.22 among those aged 6-11 months and -0.15 among those 12 months and above. Preterm birth (P=0.03), low birthweight (P<0.001) and being underweight (P=0.001) were associated with stunting. Though a low prevalence of stunting was seen, the downward shift in HAZ indicated a deficit in linear growth at the population level. This reflected the utility of HAZ as a population level marker for child undernutrition. As the prevalence of stunting among under-five children has continued to decline in Nepal, eliminating the downward shift in linear growth among under-two children can be prioritized. Potential areas of research include identification of appropriate cut-offs for maternal short stature and exploration of the epidemiological association between ponderal and linear growth among children in the local context. A consistent access to care during the antenatal period, child delivery and improved child feeding practices may have helped to improve the nutritional status among the under-two children. Assessment of linear growth along with weight gain needs to be emphasized during growth monitoring.